Prototipe Kurikulum PBI dan IKMBKM Sesuai Permendikbudristek No.53 Tahun 2023: PBI and IKMBKM Curriculum Prototype According to Permendikbudristek No. 53 of 2023 - Sirait, Jumaria; Tambunan, Marlina Agkris; Sianturi, Canni Loren; Siahaan, Mungkap Mangapul; Purba, Johannes Riscy (ITScience (Information Technology and Science), 2024)
This research is based on the paradigm of curriculum application or implementation, so the research data analysis technique uses the ADDIE method, namely Analyze, Design, Development, Implementation, and Evaluation to answer the research problem questions: (a) How is the current prototype of the PBI study program curriculum?; (b) How is the prototype of the PBI study program curriculum according to Permendikbudristek No. 53 of 2023? Thus, the purpose of the study is to determine the current PBI curriculum prototype and the PBI curriculum prototype according to Permendikbudristek No. 53 of 2023. The research was carried out in the odd semester of the 2023/2024 academic year. The research results obtained were in the form of a prototype of the PBI study program curriculum development FKIP-UHKBPNP according to Permendikbudristek RI No. 53 of 2023. Furthermore, the agile development method and prototype of the results of the curriculum development were used to be implemented in the PBI study program FKIP-UHKBPNP. The definition of development in this study is a scientific way to obtain data based on initial data, so that it can be used to produce, develop, and validate products. Product validation is also confirmed to users which is carried out through FGD, zoom, or direct meetings. The state of the arts of the research is a documentation study of the current PBI curriculum prototype and curriculum development to produce a PBI curriculum prototype according to Permendikbudristek RI No. 53 of 2023. Thus, the novelty or newness as a research finding is the PBI curriculum prototype according to Permendikbudristek RI No. 53 of 2023 which will be implemented in the PBI study program FKIP-UHKBPNP.